Narrowband ultraviolet B response in cutaneous T-cell lymphoma is characterized by increased bacterial diversity and reduced Staphylococcus aureus and Staphylococcus lugdunensis - Hooper, Madeline J.; Enriquez, Gail L.; Veon, Francesca L.; LeWitt, Tessa M.; Sweeney, Dagmar; Green, Stefan J.; Seed, Patrick C.; Choi, Jaehyuk; Guitart, Joan; Burns, Michael B.; Zhou, Xiaolong A. (Frontiers in Immunology, 2022)
Skin microbiota have been linked to disease activity in cutaneous T-cell lymphoma (CTCL). As the skin microbiome has been shown to change after exposure to narrowband ultraviolet B (nbUVB) phototherapy, a common treatment modality used for CTCL, we performed a longitudinal analysis of the skin microbiome in CTCL patients treated with nbUVB. 16S V4 rRNA gene amplicon sequencing for genus-level taxonomic resolution, tuf2 amplicon next generation sequencing for staphylococcal speciation, and bioinformatics were performed on DNA extracted from skin swabs taken from lesional and non-lesional skin of 25 CTCL patients receiving nbUVB and 15 CTCL patients not receiving nbUVB from the same geographical region. Disease responsiveness to nbUVB was determined using the modified Severity Weighted Assessment Tool: 14 (56%) patients responded to nbUVB while 11 (44%) patients had progressive disease. Microbial α-diversity increased in nbUVB-responders after phototherapy. The relative abundance of Staphylococcus, Corynebacterium, Acinetobacter, Streptococcus, and Anaerococcus differentiated nbUVB responders and non-responders after treatment (q<0.05). Microbial signatures of nbUVB-treated patients demonstrated significant post-exposure depletion of S. aureus (q=0.024) and S. lugdunensis (q=0.004) relative abundances. Before nbUVB, responder lesional skin harboured higher levels of S. capitis (q=0.028) and S. warneri (q=0.026) than non-responder lesional skin. S. capitis relative abundance increased in the lesional skin of responders (q=0.05) after phototherapy; a similar upward trend was observed in non-responders (q=0.09). Post-treatment skin of responders exhibited significantly reduced S. aureus (q=0.008) and S. lugdunensis (q=0.004) and significantly increased S. hominis (q=0.006) relative abundances compared to that of no-nbUVB patients. Staphylococcus species abundance was more similar between non-responders and no-nbUVB patients than between responders and no-nbUVB patients. In sum, the skin microbiome of CTCL patients who respond to nbUVB is different from that of non-responders and untreated patients, and is characterized by shifts in S. aureus and S. lugdunensis. Non-responsiveness to phototherapy may reflect more aggressive disease at baseline.